Finely balanced high heat conductivity, peel strength and breakdown voltage in polymer composites with binary hybrid inorganic fillers. (13th June 2018) - Peng, Cheng; Feng, Yefeng
Abstract: Nowadays, the demand of polymer based composites with high thermal conductance is rapidly increasing. Thermal conductive acrylate pressure sensitive adhesives are widely studied due to their excellent ageing resistance, light resistance, water resistance, oil resistance and broad application field. In this work, thermal conductive pressure sensitive adhesives with excellent comprehensive performances have been prepared from acrylate pressure-sensitive adhesive (matrix) and aluminum oxide/aluminum nitride particles (fillers). The influences of the class, loading content and grain size of fillers on heat conductivity, electric insulation and mechanical features of composites were deeply researched. High dispersion of fillers in matrix could be obtained by surface modification of fillers using silane coupling agent and polymethyl methacrylate. Heat conductivity of composites was improved with increasing of filler content and sharply elevated at a critical filler content. As filler content was increased, electric insulation trait was reduced but still kept at a relatively high level. High filler content was harmful to mechanical property. Fortunately, the composites with hybrid fillers of varied grain sizes were found to have significantly promoted thermal conducting, electric insulating and mechanical performances in comparison with single filler of one size. That might be ascribed to synergistic effect of both fillers with varied grain sizes. Finely balanced comprehensive features were achieved at a weight ratio of 3:7 (small size filler/large one). High heat conductivity (∼0.83 W m −1 K −1 ), breakdown voltage (∼1.9 kV) and 180° peel strength (∼8.3 kN m −1 ) were obtained. This work might open the door to the large-scale fabrication of high-performance thermal conductive acrylic pressure sensitive adhesives based on size effect of hybrid fillers.